Protective effect of sevoflurane preconditioning on ischemia-reperfusion injury in patients undergoing reconstructive plastic surgery with microsurgical flap, a randomized controlled trial. Issue 1 (December 2015) - Claroni, Claudia; Torregiani, Giulia; Covotta, Marco; Sofra, Maria; Scotto Di Uccio, Alessandra; Marcelli, Maria; Naccarato, Alessia; Forastiere, Ester
Abstract Background In many clinical conditions that involve free flaps and tissue transplantations the possibility of minimizing ischemia-reperfusion injury can be a determinant factor for the success of the surgery itself. We hypothesize that preconditioning with sevoflurane is a protective factor against ischemia-reperfusion injury. Methods In this randomized controlled trial, patients ASA I-II undergoing breast reconstruction with deep inferior epigastric perforator flaps were allocated into two groups and analyzed: group BAL included patients who received balanced anesthesia with sevoflurane for 30 min before removal of the flap and throughout the surgery. The TCI group included patients who received a total intravenous anesthesia with propofol and remifentanil. We evaluated regional tissue oximetry at the end of the surgery and at 4, 12 and 20 h after surgery. Other assessed parameters were: blood lactate clearance, alanine aminotransferase, aspartate aminotransferase, lactic dehydrogenase, creatine phosphokinase. Results In total 54 patients, twenty-seven per group, were analyzed. There was a significant increase of the average value of regional tissue oximetry measured 4 h after surgery in the BAL group compared to the TCI group: BAL: 84.05 % (8.96 SD); TCI : 76.17 % (12.92 SD) (P  = 0.03), but not at the other time frames. The creatine phosphokinase value was significantly lower in the BAL group at the end of surgery, but not at the other time-frames. There were no significant differences in blood levels of other markers. Conclusions From our results, the positive preconditioning impact of sevoflurane on ischemia-reperfusion injury in patients undergoing free flap surgery is expressed in the early postoperative hours, but it does not persist in the long-term. Trial registration ClinicalTrial.gov identifier:NCT01905501 . Registered July 18, 2013